Combined ACL and Anterolateral Reconstruction Is Not Associated With a Higher Risk of Adverse Outcomes: Preliminary Results From the SANTI Randomized Controlled Trial. Issue 5 (1st May 2020) - Sonnery-Cottet, Bertrand; Pioger, Charles; Vieira, Thais Dutra; Franck, Florent; Kajetanek, Charles; Fayard, Jean-Marie; Thaunat, Mathieu; Saithna, Adnan
Background: The widespread historical abandonment of lateral extra-articular procedures in anterior cruciate ligament (ACL) injuries occurred as a result of concerns about high rates of adverse events. Recently, the popularity of lateral extra-articular procedures has resurged, warranting an urgent evaluation of their safety profile. Purpose/Hypothesis: The aim of this study was to perform an interim analysis of the ongoing SANTI randomized controlled trial to determine whether combined ACL and anterolateral ligament reconstruction (ACL + ALLR) is associated with an increased rate of adverse outcomes when compared with isolated ACL reconstruction (ACLR). The hypothesis was that there would be no significant difference between groups at a minimum follow-up of 1 year. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: Recruitment commenced in November 2016. Patients scheduled for ACLR were randomized to either isolated ACLR (with bone–patellar tendon–bone [BPTB] autograft) or combined ACL + ALLR (with hamstring tendon autograft). All patients with a minimum follow-up of 1 year by March 2019 were included. The evaluated parameters included complications and reoperations, knee laxity parameters, range of motion, and scores on the Tegner, Lysholm, International Knee Documentation Committee (IKDC), and Knee injury and Osteoarthritis Outcome Score (KOOS) instruments. Results: A total of 224 patients (112 in each group) with a mean ± SD follow-up of 12.3 ± 1.9 months (range, 12-19 months) formed the study population. A significantly higher rate of reoperation for cyclops syndrome was noted in the isolated ACLR group compared with the combined ACL + ALLR group (8.9% vs 0%, respectively; P = .0012). No significant differences were found in frequency of graft rupture (ACLR, 5.4%; ACL + ALLR, 0.9%; P = .1191), range of motion deficits, pain, or reoperation for meniscectomy between groups. No cases of postoperative infection, venous thromboembolism, or arthrofibrosis were seen. Subjective IKDC (81.2 vs 86.8; P = .0048), Lysholm (88 vs 92; P = .0131), and some components of the KOOS were significantly better in the combined ACL + ALLR group. Conclusion: This study demonstrates no evidence of an increased risk of short-term adverse events after combined ACL + ALLR compared with isolated ACLR with BPTB graft. Registration: NCT03740022 (ClinicalTrials.gov Identifier)